REVISITING KEYNES’ INVESTMENT AND SAVING MODEL IN INDONESIA - Cheng-Wen Lee; Andrian Dolfriandra Huruta; Ramdani Putri Setyaningrum; Gatot Sasongko (Economic Review)
This study aims to analyze the Keynes’ investment and saving model in Indonesia from 1981 to 2018. The researchers use the econometric test from the Granger causality test to find the short-run causal relationship and the Vector Error Correction Model to reveal both the short-run and long-run effects in the model. The result of Granger causality test demonstrates that there is no short-run causal relationship between these two variables. In the short-run, the increase in saving affects the consumption loans more compared to the investment loans. Besides, increased consumption compared to saving has more influence in raising investment. However, the Vector Error Correction Model proves that saving negatively affects investment in the long-run. This model empirically supports the long-run Keynes’ investment and saving model. Consequently, the Indonesian government needs to consider saving as a policy instrument to increase investment in the long-run.